Optimization of Educational Mobile Game Design 'Ayo Wisata ke Riau' based on User's Perspective - Anggy Trisnadoli; Jan Alif Kreshna (UIR PRESS, 2021)
Educational Mobile Game ‘Ayo Wisata ke Riau’ is a mobile-based educational game application that was developed in 2017 on the Android platform. The quality requirements used in this game development have been adjusted for the available Educational Mobile Games. Even though it went well, there were many complaints from users during the direct implementation survey. This becomes material for re-evaluation, whether the game is ready to be disseminated to the public. Based on this occurence, a gap analysis was carried out to see the feasibility and the need for improvements to the game application that had been built. Based on the results of the gap analysis that has been carried out, it is indicated that there is a need for significant improvements in the areas of performance and user satisfaction. So that in this study, a design reengineering was carried out that was focused on improving the two things that were considered crucial, so that the results of the design and implementation that had been improved could provide better performance and user satisfaction scores than previous developments.